Dios "maestro" enseñanzas desde la sagrada escritura - Rosell de Almeida, Carlos (2010)
The intention of this brief article is to give some notions about God as "teacher" according to the information provided to us by the Holy Scriptures. In the Old Testament God is thegenuine educator of his people. On the other hand, in the New Testament, Jesus- the lncarnate Word- completes the educational work of God, becoming the master teacher.